2021
DOI: 10.1021/acs.jafc.1c05232
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Determination of Pharmaceutical and Personal Care Products in Fish Tissue Based on Matrix Solid-Phase Dispersion

Abstract: A simple and effective pretreatment method based on matrix solid-phase dispersion was developed for the determination of pharmaceutical and personal care products (PPCPs) and their metabolites in fish by high-performance liquid chromatography tandem mass spectrometry. The type and amount of dispersant, adsorbent, and eluting solvent were optimized by a single-factor experiment and Box−Behnken design. Under the optimal conditions with 2.5 g of Florisil as a dispersant, 500 mg of C 18 as an adsorbent, and 5 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The ranges of three independent variables were determined via the path of the steepest ascent method (Figure S16B−D). 44 The regression model was described by a second-order polynomial function, and its quality was evaluated by analysis of variance (ANOVA). The ANOVA analysis of the fitted second-order polynomial model determined a p-value <0.0001 (Table S7), which demonstrated that the established model was statistically significant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ranges of three independent variables were determined via the path of the steepest ascent method (Figure S16B−D). 44 The regression model was described by a second-order polynomial function, and its quality was evaluated by analysis of variance (ANOVA). The ANOVA analysis of the fitted second-order polynomial model determined a p-value <0.0001 (Table S7), which demonstrated that the established model was statistically significant.…”
Section: ■ Introductionmentioning
confidence: 99%